Tick-Borne Encephalitis Virus in Ticks and Roe Deer, the Netherlands - Jahfari, Setareh; de Vries, Ankje; Rijks, Jolianne M.; Van Gucht, Steven; Vennema, Harry; Sprong, Hein; Rockx, Barry (Emerging infectious diseases, 2017)
We report the presence of tick-borne encephalitis virus (TBEV) in the Netherlands. Serologic screening of roe deer found TBEV-neutralizing antibodies with a seroprevalence of 2%, and TBEV RNA was detected in 2 ticks from the same location. Enhanced surveillance and awareness among medical professionals has led to the identification of autochthonous cases.